Level and Rate of Population Ageing in the Northern Regions of Russia According to the New Retirement Age - Larisa A. Popova; Elena N. Zorina (Арктика и Север)
The article is devoted to the peculiarities of demographic ageing in the northern regions of Russia in accordance with the new economic threshold of old age. The relevance of the research is conditioned by the gradual increase of the retirement age in Russia and preservation of the favorable retirement age in the North. The information base is the results of the population censuses and the official data of Rosstat. The dynamic and comparative statistical analysis and demographic research methods are used. Regularities of ageing of the Russian population by new retirement age in different inter-census periods are revealed. The period of 1959-1970 is characterized by “ageing from below” due to the transition to limited fertility, and “ageing from above” under conditions of increasing life expectancy of the population. The periods of 1970-1979 and 1989-2002 are characterized by “ageing from below”. Within the periods of 1979-1989 and 2002-2010, there was a decrease in the level of ageing of the population in Russia. The last intercensal period of 2010-2021 is the only one for which the definition of “ageing from above” is suitable. By 1989, the North zone had a noticeably younger age structure of the population than in the country as a whole. The migration outflow that began in the late 1980s caused the increased rates of demographic ageing of the Northern regions, which also continued in 2002-2010. As a result, in Karelia and the Arkhangelsk Oblast, the share of the population above the new retirement age in 2021 already noticeably exceeds the average Russian level, while in the Sakhalin Oblast, the Komi Republic and the Murmansk Oblast, it is close to the national level.